Tested advertising methods - Caples, John (New Jersey: Person Education, 1997)
Contents: The new advertising strategy. The most import part of an advertisement. Headlines that attract the most readers. Right and wrong methods of writing headlines and direct mail teasers
Keywords: Publicidad